2017
DOI: 10.15678/eber.2017.050302
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of Accelerated Internationalisation of Polish and Czech Small and Medium-Sized Enterprises

Abstract: A B S T R A C T Objective:The study goal was the investigation of relationships between accelerated internationalisation descriptors and antecedent firm-and entrepreneur-related factors in Polish and Czech SMEs. Research Design & Methods:In order to compare Polish and Czech companies, the data collected in two independent studies were used. The study of 233 Polish companies was conducted with the use of CATI method in 2014; 108 Czech companies were surveyed in 2013/2014 with the use of CAWI method. In both sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…Firm characteristics are the determinant factors in the innovativeness of SMEs. Several studies confirmed the fact that firms might have different innovative posture depending on their size (Kowalik et al, 2017), sector (Civelek & Kljucnikov, 2018), area of activity (Aslesen & Harirchi, 2015), and succession involvement (Filser et al, 2018) since those characteristics make them have some advantages or disadvantages regarding capital requirements, amount of financial assets, applied strategies, firm structure. However, unlike those previous studies, this paper pays regard to all those characteristics of family-owned SMEs in a European country; thus, it would be noteworthy to investigate such a topic to fulfill the research gap.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
“…Firm characteristics are the determinant factors in the innovativeness of SMEs. Several studies confirmed the fact that firms might have different innovative posture depending on their size (Kowalik et al, 2017), sector (Civelek & Kljucnikov, 2018), area of activity (Aslesen & Harirchi, 2015), and succession involvement (Filser et al, 2018) since those characteristics make them have some advantages or disadvantages regarding capital requirements, amount of financial assets, applied strategies, firm structure. However, unlike those previous studies, this paper pays regard to all those characteristics of family-owned SMEs in a European country; thus, it would be noteworthy to investigate such a topic to fulfill the research gap.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 94%
“…Innovation also increases the SMEs' performance providing profit growth and competitive advantage, hence, they can gain opportunities to become market leaders (Laforet, 2013). Some studies analyzing Czech (Zapletalova, 2012) and Polish (Kowalik et al, 2017) SMEs indicate a reduction in internationalization time due to innovativeness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, due to a lack of financial power, micro firms are more likely to face business failure, that makes them encounter more difficulties to survive than larger businesses. Similarly, Kowalik et al (2017) state that due to having more financial and physical sources, larger firms perform better in innovativeness. Moreover, Acar and Goc (2011) and Petrakis (2005) also state that smaller firms are less likely to take risks than bigger ones.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Staffing was also found a significant factor. It is linked to the proposition about existing correlations between the managerial global vision elements and the company internationalisation scale (Kowalik, Danik, Král, & Řezanková, 2017).…”
Section: Discusion and Conclusionmentioning
confidence: 99%